The Fall of Tsähafé Teʾezaz Wäldä-Giyorgis: Reminiscences of the Victim - Zewde, Bahru (Aethiopica, 2004)
The fall in 1955 of Tsähafé Teʾezaz Wäldä-Giyorgis Wäldä-Yohannes was an event of special importance in the political history of imperial Ethiopia. For nearly a decade and a half after 1941, Wäldä-Giyorgis had exercised power and influence second only to that of Emperor Haylä-Sellasé. Yet, this very power and influence seems to have contributed to his undoing. Those who were shunted aside or feared his growing powers joined forces to estrange him from the emperor and bring about his downfall. The document printed here provides a personal account of the central character, Wäldä-Giyorgis himself, on the buildup to the final moment in May 1955, when he was removed from his powerful position to that of a provincial governor. It underscores the central role played in that downfall by his erstwhile ally, Mäkonnen Habtä-Wäld, as well as the attempt of Church authorities to mediate between the emperor and the powerful minister. Above all, the document gives us a rare insight into the relationship between emperor and minister and the trauma that the breach represented to both. Further, the outward decorum and civility that pervaded the entire proceedings of what must have been a grave political crisis provides a striking contrast to the brusqueness, not to say brutality, with which political opponents – real or imagined – were disposed of in post-1974 Ethiopia.